2016
DOI: 10.1177/1362168816643111
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of instruction on the development of second language comprehensibility, word stress, rhythm, and intonation: The case of inexperienced Japanese EFL learners

Abstract: The current study examined in depth the effects of suprasegmental-based instruction on the global (comprehensibility) and suprasegmental (word stress, rhythm, and intonation) development of 10 Japanese English-as-a-Foreign-Language (EFL) learners. Students in the experimental group (n = 10) received a total of three hours of instruction over six weeks, while those in the control group (n = 10) were provided with meaning-oriented instruction without any focus on suprasegmentals. Speech samples elicited from rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 33 publications
1
46
0
4
Order By: Relevance
“…In addition, many findings may not be applicable to K–12 contexts as a large majority of the studies have used controlled measures with adult learners of English as a foreign or second language (ESL) to ascertain improvements in pronunciation (Lee et al, ). Such measures allow researchers to control what sounds the learner produces and in what contexts, and often include simply reading aloud a set of words or sentences from a preselected text (e.g., Saito & Saito, ). In fact, a narrative literature review found that nearly 60% of studies had examined the degree to which explicit instruction in pronunciation improved learners’ performance on such discrete measures (Thomson & Derwing, ), while only 20% employed tests of spontaneous speech (e.g., Eckstein, ), with improvement on the read‐aloud tasks being easier to achieve because the context was controlled (Thomson & Derwing, , p. 331).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many findings may not be applicable to K–12 contexts as a large majority of the studies have used controlled measures with adult learners of English as a foreign or second language (ESL) to ascertain improvements in pronunciation (Lee et al, ). Such measures allow researchers to control what sounds the learner produces and in what contexts, and often include simply reading aloud a set of words or sentences from a preselected text (e.g., Saito & Saito, ). In fact, a narrative literature review found that nearly 60% of studies had examined the degree to which explicit instruction in pronunciation improved learners’ performance on such discrete measures (Thomson & Derwing, ), while only 20% employed tests of spontaneous speech (e.g., Eckstein, ), with improvement on the read‐aloud tasks being easier to achieve because the context was controlled (Thomson & Derwing, , p. 331).…”
Section: Introductionmentioning
confidence: 99%
“…Following Spada and Tomita's () task taxonomy, we first coded for controlled production tasks in which L2 learners were allowed to focus solely on accurate and fluent use of language, as in word, sentence, and paragraph reading (Saito & Saito, ) and delayed repetition tasks (Lee & Lyster, ). Our second coded category was spontaneous production tasks in which L2 learners were guided to use language accurately and fluently while at the same time using language for meaning as a primary focus, as in picture naming (Offerman & Olson, ), picture narratives (Trofimovich et al., ), timed picture descriptions (Saito, ), and interviews (Parlak & Ziegler, 2016).…”
Section: Research Synthesis and Meta‐analysismentioning
confidence: 99%
“…Further research should test this principle in larger samples because one limitation of our study is related to the small number of learners who were effectively assessed by school to identify a proficiency level. Additionally, effects of instruction should be revisited in order to understand the weaknesses for the L2 learners [30]. The SES variable showed to have influence for comprehensibility in these L2 learners, as shown in the children with unemployed parents, which were in the lowest position.…”
Section: Discussionmentioning
confidence: 99%